Evaluation of Transparency and Accountability of Regional Government Financial Reports (LKPD) in Realizing Good Governance - Feri Hardiyanto (Journal of Taxation Insights Policy Practice, 2025)
Transparency and accountability in Regional Government Financial Reports (LKPD) are key to achieving good governance, yet challenges such as limited resources and political pressure often hinder effective implementation. This study evaluates the extent to which LKPDs reflect good governance principles in Indonesia, given the importance of transparent and accountable regional financial management for building public trust and improving government efficiency. Specifically, it analyzes the level of transparency and accountability in LKPDs, identifies supporting and inhibiting factors, and assesses their contribution to good governance, focusing on regional governments across multiple provinces. Using a qualitative descriptive-analytical approach with a purposive sampling method, data were collected through interviews, observations, document analysis, and questionnaires with government officials, Audit Board of the Republic of Indonesia (BPK) auditors, and stakeholders. Analysis followed the Miles and Huberman model: data reduction, presentation, and verification. Results show that 72% of regions achieved an Unqualified Opinion (WTP) from BPK, while 28% received Qualified or Disclaimer opinions. Key obstacles include limited human resources, political pressure, and low public participation. High-quality LKPDs are strongly associated with improved governance outcomes. The study implies that sustained capacity building, technology integration, and stronger stakeholder coordination are essential to enhance transparency, accountability, and ultimately, public sector performance.